The Relationship Between Physical Activities, Consumption Pattern, Body Image and Nutritional Status of High School Students - Mukhtar Efendi; Didik Cahyono; Ilham Arief; Singgih Prastawa; Dasep Supriatna (Departement of Mathematics Education, 2023)
In order for the body to perform biological activities including physical growth, development, exercise, maintaining health, and others, there must be a balance between the nutrients that are consumed and those that are needed by the body. Riskesdas reports an increase in the prevalence of obesity and wasting among teenagers between the ages of 16 and 18. In this study, it will be determined whether there is a connection between female students' nutritional status, eating habits, and physical activity. using the aid of a cross-sectional study strategy. There were 85 pupils in the research sample. Using the chi-square statistical test, univariate and bivariate analysis of the data was performed. According to the findings, 65.4% of female students used relatively little energy. The bivariate analysis revealed that body image (p = 0.037), energy consumption (p = 0.001), carbohydrate intake (p = 0.002), protein intake (p = 0.000), and fat intake (p = 0.000) were the factors that were most strongly associated with the nutritional status of female students